2016
DOI: 10.1080/13557858.2016.1244740
|View full text |Cite
|
Sign up to set email alerts
|

Balancing satisfaction and stress: carer burden among White and British Asian Indian carers of stroke survivors

Abstract: Since the role of carers is clearly indispensable in the successful rehabilitation of survivors, it is vital to ensure that their well-being is not undermined by a lack of information and training, and that their need for professional support is prioritised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…A qualitative study showed that the emotional and physical well-being of caregivers of people with sequelae of stroke was impaired because of the uncertainty and unpredictability of the time of care, in addition to their expectations and misunderstood needs. The responsibility to care for other people was a factor that influenced the increase in tension (31) . The social changes evaluated by the items "time for activities with the family, " "time for activities with the friends" and "social roles" obtained, respectively, the scores 2.79, 2.77 and 3.79, the lowest means, except for the item that assesses the change in social roles.…”
Section: Discussionmentioning
confidence: 99%
“…A qualitative study showed that the emotional and physical well-being of caregivers of people with sequelae of stroke was impaired because of the uncertainty and unpredictability of the time of care, in addition to their expectations and misunderstood needs. The responsibility to care for other people was a factor that influenced the increase in tension (31) . The social changes evaluated by the items "time for activities with the family, " "time for activities with the friends" and "social roles" obtained, respectively, the scores 2.79, 2.77 and 3.79, the lowest means, except for the item that assesses the change in social roles.…”
Section: Discussionmentioning
confidence: 99%
“…Following the event, caregivers detailed their lack of knowledge as maintaining their uncertainty. Specifically, they reported an inability to “know” the cause of the event [ 26 , 30 , 34 ], the stroke survivors’ prognosis [ 25 , 27 , 29 , 31 , 32 , 33 , 34 , 35 ], the safety of the survivor if left alone [ 24 , 27 , 29 , 30 , 36 ], the support options available [ 27 , 29 , 35 , 36 ], and how to provide care to the survivor [ 27 , 30 , 34 , 35 , 36 ]. While only expressed by some caregivers in one study [ 35 ], the loss of intimacy with and lack of empathy from survivors also contributed to uncertainty.…”
Section: Resultsmentioning
confidence: 99%
“…As a result of this uncertainty, caregivers reported worries about their abilities to successfully navigate their newfound responsibilities. Specifically, they noted concerns about their abilities to manage finances [ 24 , 35 , 36 ], effectively plan for the future [ 24 , 26 , 29 ], identify others who would assume caregiving responsibilities for the survivor if they themselves fell ill [ 25 , 27 , 35 ], and ways to cope with the stroke event [ 26 , 35 ]. The lack of clarity surrounding these concerns resulted in feelings of hopelessness [ 24 , 25 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It identifies support for carers (family members, friends or neighbours who provide help and assistance to someone) as a global public health issue with a focus on maintaining carer well-being (Zwingmann et al, 2020). The impact of the caring role and the stressors carers can experience when supporting people with complex care needs are well documented (Katbama et al, 2016;Farina et al, 2017;Temple and Bow, 2018). The provision of short breaks is identified as a means of sustaining caring relationships.…”
Section: Introductionmentioning
confidence: 99%